2011
DOI: 10.2217/rme.11.83
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Umbilical Cord Mesenchymal Stem Cell Infusion for the Treatment of Combined Malnutrition Nonunion of the Humerus and Radial Nerve Injury

Abstract: Nonunion and nerve injury are the most severe and common complications of bone fracture treatments. There is still no ideal therapy for these two complications. In this report, we first applied umbilical cord mesenchymal stem cell (UC-MSC) therapy to one patient with both nonunion and nerve injury, and observed the therapeutic effects. UC-MSCs were produced and expanded according to a clinical-grade technique using serum-free medium enriched in human platelet lysate. Flow cytometry was performed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
9
0
3
Order By: Relevance
“…17,18 The MSCs isolated from other sources share many common features with BM-MSCs, 19,20 and have been applied in tissueengineering strategies. [21][22][23][24][25] Nevertheless, only a few papers documented the paracrine or autocrine effects of adipose tissue-derived MSCs in tissue regeneration. 26,27 The trophic effects of MSCs isolated from a nonbone marrow origin have not yet been systematically and thoroughly studied.…”
mentioning
confidence: 99%
“…17,18 The MSCs isolated from other sources share many common features with BM-MSCs, 19,20 and have been applied in tissueengineering strategies. [21][22][23][24][25] Nevertheless, only a few papers documented the paracrine or autocrine effects of adipose tissue-derived MSCs in tissue regeneration. 26,27 The trophic effects of MSCs isolated from a nonbone marrow origin have not yet been systematically and thoroughly studied.…”
mentioning
confidence: 99%
“…It is only recently that CT stem cells have made their way into the clinic; and it is only now that clinical comparisons to bone marrow MSCs can be made. A recent report from Xue et al examined the use of CT-MSCs in patients with non-healing bone fractures [71]. This study reported significant clinical benefit from intravenously infused MSC.…”
Section: Common Stem Cell Usesmentioning
confidence: 90%
“…In fact, when CB stem cells were placed into animals with fractured femurs there was significant bone healing. A recent report from Xue et al examined the use of CT MSCs in patients with non-healing bone fractures [71]. This study reported significant clinical benefit from intravenously infused MSC.…”
Section: Ctmentioning
confidence: 91%
“…The cryo-container is generally mixed at 4 °C for 20–30 min to allow for cryoprotectant equilibration. Cryopreservation is performed using a controlled rate freezer to −180 °C before final submersion in liquid nitrogen for long term storage [71]. In our experience we have not seen significant differences in AT-MSC harvest by tumescent liposuction, VASER liposuction, power-assisted liposuction or various forms of laser liposuction (although we have not analyzed all possible permutations that are commercially available).…”
Section: Stem Cell Banking Approachesmentioning
confidence: 92%
“…A recent report from Xue et al . examined the use of CT-MSCs in patients with non-healing bone fractures [71]. This study reported significant clinical benefit from intravenously infused MSC.…”
Section: Common Stem Cell Usesmentioning
confidence: 99%